2009
DOI: 10.1016/j.jvs.2009.07.085
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Year Experience with Combined Vascular Reconstruction and Free Flap Transfer for Limb-Salvage

Abstract: recorded. ABI Ͻ 0.9 was considered equivalent to moderate-to-high CHD risk (Ն10%).Results: ABI Ͻ 0.9 prevalence was 4.5%. Only 0.62% presented low ABI and IC. Age, current smoker, cardiovascular disease, and uncontrolled hypertension independently associated with ABI Ͻ 0.9 in both sexes; IC was also associated in men and diabetes in women. Among participants 35-74 free of cardiovascular disease, 6.1% showed moderate-to-high 10-year CHD risk; adding ABI measurement yielded 8.7%. Conversely, the risk function id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 0 publications
2
35
0
2
Order By: Relevance
“…Therefore, these three articles were additionally excluded. Finally, 30 articles overlooking 1,356 patients and 1,397 free flaps for lower extremity reconstruction were included in the present meta‐analysis (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these three articles were additionally excluded. Finally, 30 articles overlooking 1,356 patients and 1,397 free flaps for lower extremity reconstruction were included in the present meta‐analysis (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Free tissue transfer in conjunction with direct surgical revascularization, whether staged or simultaneous, has become an accepted form of treatment for patients with severe distal disease, limb‐threatening ischemia, and otherwise non‐reconstructible arterial occlusive disease and soft tissue loss . Patients otherwise destined for leg amputation may achieve reliable limb salvage following arterial reconstruction and free flap coverage . Nevertheless, the combination of free tissue transfer and arterial bypass grafting for ischemic lower extremity wounds has been shown to be a high‐risk and complex procedure with poor long‐term success in patients with diabetes and end‐stage renal disease .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Patients otherwise destined for leg amputation may achieve reliable limb salvage following arterial reconstruction and free flap coverage. 29,30 Nevertheless, the combination of free tissue transfer and arterial bypass grafting for ischemic lower extremity wounds has been shown to be a high-risk and complex procedure with poor long-term success in patients with diabetes and end-stage renal disease. 18,30 Detailed knowledge of arterial vessel predominance and directional flow in these complex wounds can guide the plastic and vascular surgeons in designing the best reconstructive and revascularization treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Oh et al have also reported that, 6 in their series of 113 diabetics, who underwent successful free flap transfer for foot ulcerations, the patients had a higher 5-year survival rate compared with those who were not treated. Most studies today would agree that despite the potential costs of limb salvage, it is still far cheaper compared with the costs of multiple unsuccessful local flaps and eventual amputation.…”
Section: Discussionmentioning
confidence: 96%
“…Although this type of surgery is technically challenging compared with most other free flap transfers, it can be successful and very rewarding in terms of limb salvage in the affected patients. 12 Further, in 2010, Kim suggested that perforator flaps using "supermicrosurgery" could be successfully performed in these patients, perhaps obviating the need for an open major vessel for anastomosis. 2 We did, however, note that the complication rate was fairly high, but this was mostly limited to wound-healing issues.…”
Section: Discussionmentioning
confidence: 99%